2002
DOI: 10.1038/sj.bjc.6600079
|View full text |Cite
|
Sign up to set email alerts
|

Ciprofloxacin induces apoptosis and inhibits proliferation of human colorectal carcinoma cells

Abstract: Efficacy of chemotherapy in advanced stages of colorectal tumours is limited. The quinolone antibiotic ciprofloxacin was recently shown to inhibit growth and to induce apoptosis in human bladder carcinomas cells. We investigated the effect of ciprofloxacin on colon carcinoma lines in vitro. CC-531, SW-403 and HT-29 colon carcinoma and HepG2 hepatoma cells (control cells) were exposed to ciprofloxacin. Proliferation was assessed by bromodeoxyuridine-incorporation into DNA and apoptosis was measured by flow cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
100
1
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(115 citation statements)
references
References 25 publications
13
100
1
1
Order By: Relevance
“…20,39 Importantly, the pro-apoptotic effects appear to be cancer cell-specific, as illustrated in a study showing that nontumorigenic prostate epithelial cells (MLC8891) were not affected when treated in parallel to malignant PC3 prostate cells. 19 It was suggested that CPFX could be a potential chemotherapeutic agent for treatment of a range of cancers, e.g., bladder and prostate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20,39 Importantly, the pro-apoptotic effects appear to be cancer cell-specific, as illustrated in a study showing that nontumorigenic prostate epithelial cells (MLC8891) were not affected when treated in parallel to malignant PC3 prostate cells. 19 It was suggested that CPFX could be a potential chemotherapeutic agent for treatment of a range of cancers, e.g., bladder and prostate.…”
Section: Discussionmentioning
confidence: 99%
“…Related effects were also observed in WTK1 and NH32 cells (and to a lesser extent in PHA-stimulated lymphocytes), however, G 2 arrest was not apparent until 24 h. A number of different cell types including CC-531, SW-403 and HT-29 colon carcinoma cells, MC3T3-E1 and MG-63 osteoblast-like cells and HTB9 bladder carcinoma cells show time-dependent G 2 M cell cycle arrest following exposure to similar concentrations of CPFX. 20,21,39 Aranha et al, 20 reported that CPFX treatment, at least in HTB9 cells, produced a downregulation in cyclins B and E, and dephosphorylation of cyclin-dependent kinase-2 and thereby causing G 2 M arrest. Although we provide limited evidence, we hypothesize that ATM P1981 triggers the signaling cascade, which is ultimately responsible for G 2 arrest (and apoptosis) in these cancer cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Our group and others assessed the in vitro activity of certain quinolones against various tumour cell lines. Ciprofloxacin was found to inhibit tumour cell growth of bladder transitional cell carcinoma, colon cancer and prostate cancer cell lines at concentrations achievable with its oral administration (Zehavi-Willner and Shalit, 1992;Shalit et al, 1995;Herold et al, 2002;Aranha et al, 2003).…”
mentioning
confidence: 99%
“…Quinolones are known for their antibacterial and antitumor activities through alteration of the normal functions of bacterial gyrase, and are found to be a topoisomerase II inhibitor in humans [9][10][11][12][13][14][15][16][17][18] . Ciprofloxacin (Figure 1), a commonly used broadspectrum fluoroquinolone antibiotic, has shown anticancer activity in several cancer cell lines 19,20 . Other fluoroquinolone derivatives such as levofloxacin and ofloxacin have also been shown to inhibit the growth of cell bladder cancer cell lines (Figure 1) 21 .…”
Section: Introductionmentioning
confidence: 99%